Boolean modeling reveals that cyclic attractors in macrophage polarization serve as reservoirs of states to balance external perturbations from the tumor microenvironment - de León, Ugo Avila-Ponce; Vázquez-Jiménez, Aarón; Matadamas-Guzmán, Meztli; Resendis-Antonio, Osbaldo (Frontiers in Immunology, 2022)
Cyclic attractors generated from Boolean models have been frequently considered mathematical artifacts without any biological relevance. Conversely to this idea, we postulate that cyclic attractors in certain cases could be a systemic mechanism to face the perturbations coming from the environment. To justify our conjuncture, we present a dynamic analysis of a high-curated transcriptional regulatory network of macrophages constrained into a cancer microenvironment. We observed that when M1-associated transcription factors (STAT1 or NF𝜿B) are perturbed and the microenvironment balance to a hyper-inflammation condition, cycle attractors activate genes whose signals counteract this effect implicated in the damage of the tissue. The same behavior happens when the M2-associated transcription factors are disturbed (STAT3 or STAT6), cycle attractors will prevent a hyper-regulation scenario implicated in providing a suitable environment for tumor growth. Therefore, here we propose that cyclic macrophage phenotypes can serve as a reservoir for balancing the phenotypes when a specific phenotype-based transcription factor is perturbed in the regulatory network of macrophages. We consider that cyclic attractors should not be simply ignored but it is necessary to carefully evaluate their biological importance. In this work we suggest one conjecture: the cyclic attractors can serve as a reservoir to balance the response inflammatory/regulatory of the network under external perturbations.